Realization of Direct Current System Insulation Monitoring Device Based on Fault Amplifying Method - Zhou Jun; Yang Sheng-qiang; Zhu Bo-nan (Institute of Advanced Engineering and Science, 2014)
This paper has analyzed the existing direct current (DC) system insulation monitoring methods. In view of poor anti-jamming and low sensitivity of existing methods, a new insulation monitoring device is designed based on Fault amplifying method. Under the condition of ensuring system security, the device detection resistors are put into the system by control switches, data is collected by the sensors and set to host computer by CAN bus. At last, the host determines insulation condition of the system by calculating the insulation resistances. This paper has introduced the main test circuit and program flow chart. It is verified by experiments and field operation that the device which is perfectly suitable for online DC insulation monitoring of power plants and transformers can monitor the insulation condition of system accurately and the sensitivity is high. DOI: http://dx.doi.org/10.11591/telkomnika.v12i6.5486